Effect of joint interface conditions on shear transfer behavior of recycled aggregate concrete. (15th February 2016) - Xiao, Jianzhuang; Sun, Chang; Lange, David A.
Highlights: Effect of joint interface conditions on shear transfer behavior of RAC was tested. RCA replacement ratio negatively affects the aggregate interlock action of RAC. The shear stress in RAC with uncracked or cold-joint interfaces was predicted. Abstract: In this study, 38 uncracked and cold-joint push-off specimens were tested to explore how joint interface characteristics affect shear transfer behavior of recycled aggregate concrete (RAC). The major test variables included the recycled coarse aggregate (RCA) replacement ratio and joint interfaces. The results indicate that the shear transfer behavior of RAC with different joint interfaces is similar to that of conventional concrete. It was shown that the RCA replacement ratio has some effect on the ultimate shear transfer strength. The joint interface has great influence on the shear transfer behavior of RAC. Aggregate interlock, bond, and doweling action are aspects of the joint surface condition that effect shear transfer. The RCA replacement ratio negatively affects the aggregate interlock action of RAC. This paper demonstrates that design equations in ACI and PCI codes are conservative and effective for predicting the shear stress in RAC specimens with uncracked or cold-joint interfaces.